Determinants Of The Level Of Corporate Risk Disclosure In Manufacturing Companiesyear 2017-2021 - Destika Wulandari; Yudi Partama Putra (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of the Independent Board of Commissioners, External Auditor Quality, Competition, Company Size, Profitability and Leverage on Corporate Risk. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021, totaling 193 companies. While the sample obtained was 45 companies. The sampling technique used purposive sampling technique, the research method is quantitative method. The data analysis used in this study is multiple linear regression analysis processed using SPSS 26. The results showed that the independent board of commissioners has no effect on company risk, the quality of external auditors has no effect on company risk, competition has an influence on company risk, company size has an influence on risk, profitability has no effect on company risk, and leverage has an influence on company risk.